Imigrantes, xenofobia e racismo: uma análise de conflitos em escolas municipais de São Paulo - Oliveira, Leila Maria de (2019)
This research aims at analyzing the conflicts related to the presence of immigrant students and children of immigrants in the municipal schools of Sao Paulo. The qualitative methodology is adopted in this work, with the data collected being predominantly descriptive and explanatory. Thus, the literature review conducted here allowed us to better understand the history and the cleavages related to migratory movements in Brazil and its influences on the education system. We have investigated policies at national, state and municipal levels that offer an intersection with the expectations of learning experiences meant to confront xenophobia and racism in an intercultural approach. The adoption of the ethnographic method allowed the observation in locus and the interpretation of possible conflicts caused by the presence of immigrants in the daily school life. The research revealed a close relationship between xenophobia-racism and the hierarchies attributed to the different groups of immigrants: those with western phenotypes tend to be integrated more easily while learning Portuguese and immigrants with non-western phenotypes find more difficulties, even when Portuguese is their mother tongue. It is hoped that this study will be an incentive to the elaboration of education policies and to pedagogical projects in schools that receive immigrant students, as well as practices and studies focused on valuing the differences in the classroom